PENGARUH KONSELING KELOMPOK TERHADAP KEDISIPLINAN SHALAT BERJAMAAH REMAJA DI MUSHALLA MUHSIN HADIR DUGHAIMAN KOMPLEK PESONA FILANO KOTA PADANG - s, mansyur (Journal of Contemporary Islamic Counselling, 2023)
This research is based on the phenomenon that occurred in the Musahlla Muhsin Hadir Dughaiman Komplek Pesona Filano Padang City, it was seen that many teenagers were present at the mushalla during congregational prayers but did not attend congregational prayers with discipline and order. The purpose of this experimental research is to see to what extent group guidance can improve youth order and discipline in praying together. The method used in this study is a research experiment using a quantitative approach. The type of design used in this study is One Shot Case Study, an experiment without a control/comparison group using a pretest and after being given treatment, the measurement is carried out again through the posttest to find out and understand the impact/effect of the treatment or action that has been given, so that It can be seen how much influence or effect of the treatment that has been given.The results showed that there was a change in the value of discipline from the previous 23.1% after being given treatment, increasing to 53.8%.